Up-Regulation of TLR7-Mediated IFN-α Production by Plasmacytoid Dendritic Cells in Patients With Systemic Lupus Erythematosus - Sakata, Kei; Nakayamada, Shingo; Miyazaki, Yusuke; Kubo, Satoshi; Ishii, Akina; Nakano, Kazuhisa; Tanaka, Yoshiya (Frontiers in Immunology, 2018)
Objectives: Aberrant and persistent production of interferon-α (IFN-α) by plasmacytoid dendritic cells (pDCs) is known to play a key role in the pathogenesis of systemic lupus erythematosus (SLE). To assess the precise function of pDCs in SLE patients, we investigated the differential regulation of Toll-like receptor 7 (TLR7) and TLR9 responses during IFN-α production by pDCs. Methods: Peripheral blood mononuclear cells (PBMCs) in SLE patients without hydroxychloroquine treatment, rheumatoid arthritis patients and heathy controls were stimulated with TLR7 and TLR9 agonists. To investigate the priming effect by cytokines, PBMCs from healthy controls were pre-treated with various cytokines and stimulated with TLR7 and TLR9 agonists. The IFN-α production in pDCs was detected by flow cytometry. Results: TLR7-mediated IFN-α production was up-regulated and correlated positively with disease activity in SLE. Conversely, TLR9-mediated IFN-α production was down-regulated. Differential regulation of TLR7/9 response in SLE was independent of TLR7 and TLR9 expression levels. Furthermore, in vitro experiments indicated that TLR7-mediated IFN-α production was up-regulated by pre-treatment with type I IFN, whereas TLR9-mediated IFN-α production was down-regulated by pre-treatment with type II IFN. Conclusions: Our study indicates the association between up-regulation of TLR7- mediated IFN-α production by pDCs and disease activity and that TLR7 and TLR9 responses were reversely regulated on pDCs in SLE patients. Thus, type I IFN and TLR7-mediated IFN-α production were involved in a vicious cycle, causing hyper production of IFN-α by pDCs during the pathogenic processes of SLE.